Daylight photodynamic therapy in Scotland. Issue 2 (May 2017) - Cordey, Helen; Valentine, Ronan; Lesar, Andrea; Moseley, Harry; Eadie, Ewan; Ibbotson, Sally
Chronic sun-induced dysplastic skin changes (actinic keratoses) are extremely common in fair-skinned people in Scotland. These changes are a major cause of morbidity and may develop into skin cancer. Actinic keratoses are often extensive and pose a therapeutic challenge as field-directed treatment is required for chronic disease management. One such treatment approach is hospital-based photodynamic therapy, which is a well-established treatment in Scotland for actinic keratoses, using a photosensitiser pro-drug and red LED light irradiation. However, photodynamic therapy using daylight as the activating light source is increasingly and effectively used in continental Europe, but had not been explored in Scotland until we initiated this in 2013. We report our experience of daylight photodynamic therapy in 64 patient-treatment courses and demonstrate that this can be an effective, well-tolerated treatment, which is liked by patients. Our most recent data show that most patients (73%) achieved clearance or at least a good response to treatment and had high levels of satisfaction with daylight photodynamic therapy. Daylight exposure measurements indicated that treatment is feasible in Scotland between April to September. Daylight photodynamic therapy is an important advancement in treatment options for Scottish patients with extensive pre-cancerous field changes and provides opportunities for home-based treatment and increased efficiency of photodynamic therapy services.